Electrochemotherapy induces tumor regression and decreases the proliferative index in canine cutaneous squamous cell carcinoma - Dos Anjos, Denner S.; Bueno, Cynthia [UNESP]; Magalhães, Larissa F.; Magalhães, Georgia M.; Mattos-Junior, Ewaldo; Pinto, Marcela M. R.; De Nardi, Andrigo B. [UNESP]; Brunner, Carlos H. M.; Leis-Filho, Antonio F. [UNESP]; Calazans, Sabryna G.; Fonseca-Alves, Carlos E. [UNESP] (Springer Nature, 2019)
Canine cutaneous squamous cell carcinoma (cSCC) is the most common skin cancer in dogs, and, due to its low metastatic rate, local treatments, such as electrochemotherapy (ECT), promote disease control or even complete remission (CR). This study aimed to evaluate the gene and protein expression of Bcl-2 and Bcl-2 associated X protein (BAX), the proliferative index and clinical parameters in dogs with cSCC subjected to ECT. A prospective nonrandomized clinical study was performed using dogs with naturally occurring cSCC that was treated with ECT. Eighteen lesions from 11 dogs were selected. The tumor size at day 0 (D0) had no impact on survival or prognosis (P > 0.05). Tumor samples had a lower proliferative index after ECT (D21) than before ECT (P = 0.031). The survival of subjects with Ki67 values lower and higher than the Ki67 median value were not significantly different (P > 0.05). Regarding apoptotic markers, there were no significant differences in the gene and protein expression levels of BAX or Bcl-2 at D0 and D21 (P > 0.05) or in the overall survival of subjects with different levels of apoptotic markers. In conclusion, there was no change in BAX or Bcl-2 gene and protein expression in response to ECT at the time points evaluated, but ECT was able to reduce tumor volume and cellular proliferation in cSCC.